From Text Analysis to Reader’s Autobiography: Towards a Didactics of Literary Reading (inOpera Esercizi di lettura su testi contemporanei, 2024)
Commentary reading and text analysis have had a prominent place in literary teaching in secondary schools for about fifty years. The article aims to highlight the reasons for this primacy and its effects on a school system that is also experimenting with new teaching models that assign commentary and textual analysis a renewed role as a result of studies in the didactics of literature.